PENGARUH KOMUNIKASI HORIZONTAL TERHADAP PENINGKATAN PENJUALAN AYAM PENYET SURABAYA JL. DR. MANSYUR - Masliana Tarigan; Emmelia Ginting (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
This study aims at determining how horizontal communication affects increasing sales at Surabaya's Penyet Chicken on Jalan Dr. Mansyur Medan. The research method used in this research is quantitative descriptive using the Alpha formula. The population in this research is all employees working at Surabaya's Penyet Chicken, amounting to 29 people and the sample used is total sampling. The results show that there was a low but certain effect between horizontal communication (X) on increasing sales of Surabaya Penyet Chicken (Y).